INFORMATION DISSEMINATION STRATEGIES TO FACILITATE THE EXAMINATION PROCESS: A CASE STUDY OF FSPPP EXAM KIT - Noorie Haryaniee Moulton; Nor Ezrine Yusoff; Jeniwaty Mohd Jody; Nasyrah Ahmad; Nurul Hidayana Mohd Noor; Ummi Ramizahana Rosli, (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2024)
The development of the Internet led to the development of various communication mediums such as websites, mobile phones, and social networking systems. The physical limitations and constraints of conventional media in conveying information can be overcome with the emergence of digital media technology. Thus, the research has been carried out to examine the effectiveness of a new examination information dissemination approach, which is also known as the FSPPP Exam Kit. The study examines the student perception of the kit and assesses the outcome of the kit implementation. This includes disciplinary issues such as cheating, improper dress code, missing examination slips, and late/absenteeism for examination. This study uses a quantitative approach and a questionnaire to collect information. The study population includes students from the Faculty of Administrative Science and Policy Studies, Universiti Teknologi MARA (UiTM), Seremban, as many as 2000 students. The sample size involved 322 systematic randomly selected respondents. The data was analyzed using descriptive and inferential analysis. The study results found that most students have widely accepted this kit, and it helps reduce examination disciplinary issues. Moreover, a significant negative relationship exists between kit effectiveness and disciplinary cases. The kit can be an alternative to the faculty's formal communication tool with appropriate improvements. The kit helps them get information, interact with each other, and improve their knowledge about the examination procedures. This study reveals the importance of websites and new media in delivering information to university stakeholders.